Alveolar rhabdomyosarcoma of urinary bladder presenting as acute leukemia: A diagnostic trap - Rakhi V Jagdale; Jaydeep N Pol (Wolters Kluwer Medknow Publications, 2020)
Rhabdomyosarcoma (RMS) masquerading as acute leukemia (AL) is very rare. We report a case which presented as acute leukemia subsequently diagnosed to be Alveolar RMS of Urinary Bladder. Although cases of RMS with leukemic presentation have been reported, to our knowledge this is the first case of Alveolar RMS of Urinary Bladder with leukemic picture at initial presentation. We would like to emphasize that this critical error can have serious consequences on the treatment and outcome of these patients.